2016
DOI: 10.1111/tog.12280
|View full text |Cite
|
Sign up to set email alerts
|

Complications of caesarean section

Abstract: Key content The incidence and presentation of complications of caesarean section. The surgical management of intrapartum and postpartum haemorrhage. Risk factors for, and prevention and treatment of postpartum sepsis. Presentation, investigation and repair of bladder injuries when recognised intraoperatively and following delayed presentation. Risk factors for, and recognition and management of suspected ureteric injury intraoperatively and postoperatively. Bowel complications including intraoperative bowel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 37 publications
0
53
0
1
Order By: Relevance
“…In developing countries, obstetric hemorrhage alternates the first and second position with preeclampsia as a cause of maternal death, and the World Health Organization accepts a rate of 10% worldwide in all births with live fetus [3,4,[14][15][16][17][18][19][20][21].…”
Section: Hemorrhagementioning
confidence: 99%
See 2 more Smart Citations
“…In developing countries, obstetric hemorrhage alternates the first and second position with preeclampsia as a cause of maternal death, and the World Health Organization accepts a rate of 10% worldwide in all births with live fetus [3,4,[14][15][16][17][18][19][20][21].…”
Section: Hemorrhagementioning
confidence: 99%
“…This increase is also favored by non-professional communication in social networks that minimize the surgical risks of cesarean section, promoting false advantages aimed mainly at family comfort; as well as by health professionals not related to obstetrics and although it bother us to recognize it, also by some "obstetricians" who seek personal benefits [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nulliparous women have an increased risk of Caesarean delivery after induction of labour 3,4 . Caesarean section is associated with short-term and long-term complications such as postpartum haemorrhage, morbid adherence of placenta, and uterine rupture in future pregnancies [5][6][7] . Risk factors for Caesarean delivery after induction of labour include nulliparity, more advanced maternal age, greater body mass index, hypertension, and diabetes [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Cesarean Section (CS) rates have been increasing in recent decades worldwide, and this is a global problem because of the negative effect on maternal and neonatal health [ 1 ]. Although CS is a very common surgery, it is associated with an increased risk of hemorrhage, uterine bladder and bowel injury, postoperative sepsis, postoperative ileus [ 2 ] and thromboembolic events [ 3,4 ]. Some studies on neonatal complications have shown that CS is associated with an increased risk for the infant's obesity, diabetes, respiratory morbidity, and atopic dermatitis in childhood [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%